2012
DOI: 10.1111/j.1471-0307.2012.00862.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an autochthonous starter culture and a commercial starter on the characteristics of Tenerife pasteurised goats’ milk cheese

Abstract: Two batches of Tenerife cheese were produced from pasteurised goats’ milk, one with a commercial starter and another with an autochthonous starter consisting of three selected strains of lactic acid bacteria isolated from artisanal Tenerife cheese. Influence of starter on the characteristics of the cheeses was evaluated. Owing to the composition of the starters, lactobacilli and leuconostocs varied significantly between both cheeses. However, the type of starter did not significantly affect the physicochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
(30 reference statements)
1
6
0
1
Order By: Relevance
“…minimum and maximum water-soluble and TCA-soluble N fractions of Gokceada goat cheeses ranged between 3.48 and 16.56 and 2.49 and 13.80, respectively (Hayaloglu et al 2013a). Similar results were also found by other studies on Gokceada goat cheese by Hayaloglu et al (2013b), and Gonzalez and Zarate (2012) reported that water-soluble fractions in TN (WSN/TN) of Tenerife cheese made using commercial or autochthonous starter cultures ranged between 12.12 and 24.88% during 90 days of ripening. Bontinis et al (2012) investigated the level of nitrogen fractions of a traditional Greek goat cheese (Xinotyri) during 180 days of ripening.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…minimum and maximum water-soluble and TCA-soluble N fractions of Gokceada goat cheeses ranged between 3.48 and 16.56 and 2.49 and 13.80, respectively (Hayaloglu et al 2013a). Similar results were also found by other studies on Gokceada goat cheese by Hayaloglu et al (2013b), and Gonzalez and Zarate (2012) reported that water-soluble fractions in TN (WSN/TN) of Tenerife cheese made using commercial or autochthonous starter cultures ranged between 12.12 and 24.88% during 90 days of ripening. Bontinis et al (2012) investigated the level of nitrogen fractions of a traditional Greek goat cheese (Xinotyri) during 180 days of ripening.…”
Section: Discussionsupporting
confidence: 87%
“…Similar results were also found by other studies on Gokceada goat cheese by Hayaloglu et al . (), and Gonzalez and Zarate () reported that water‐soluble fractions in TN (WSN/TN) of Tenerife cheese made using commercial or autochthonous starter cultures ranged between 12.12 and 24.88% during 90 days of ripening. Bontinis et al .…”
Section: Discussionmentioning
confidence: 99%
“…The starter culture had a statistically significant effect ( < 0.05) on odor, taste, and general acceptance (Table 4); these samples had an intense and typical goat flavor attributes that consumers expect to find in goat products and a slightly acidic taste. Similarly, other authors have reported aroma intensity to be higher in cheeses made with an autochthonous culture [6,34,35]. Commercial starter batch had the lowest scores in taste, odor, and general acceptance due its highly acidic taste and the absence of characteristic goat flavor.…”
Section: Effect Of Pasteurization Temperaturementioning
confidence: 92%
“…The use of autochthonous cultures is not widespread yet,; therefore it is essential to study the effect of autochthonous starter culture in spreadable goat cheese. Because of the growing interest in preserving the typical sensory properties of traditional cheeses, there is an increasing demand for autochthonous strains to replace or complement existing commercial starters currently used by the dairy industry [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Diferentes autores han aislado bacterias lácticas autóctonas a partir de leche de cabra (Alonso-Calleja et al, 2002;Nikolic et al, 2008;González y Zárate, 2012;Perin y Nero, 2014) y quesos artesanales (Cogan et al, 1997;Pérez-Erlotondo et al, 1998;Fraga-Cotelo et al, 2013;Terzic-Vidojevic et al, 2014), con el objetivo de identificarlas y caracterizar sus propiedades funcionales o tecnológicas en los procesos de elaboración y maduración de quesos; o bien con la intención de incluirlas como cultivos iniciadores, posibilitando la producción industrial de quesos con características similares a las artesanales. La selección de cepas autóctonas con propiedades deseables podría lograr una producción estandarizada, mejorar la calidad sensorial y al mismo tiempo preservar las características que definen la identidad de un queso artesanal (Pavunc et al, 2012;Speranza et al, 2015).…”
Section: Introductionunclassified